PROPORSIONALITAS DALAM PENJATUHAN PIDANA TERKAIT ADANYA DISPARITAS PIDANA DALAM PERKARA NARKOTIKA - Muhammad Naim (Legal Standing : Jurnal Ilmu Hukum, 2018)
The research entitled Principles Of Proportions In Cases Of Criminal Handling Connected With The Case Discussion Of Narcotics is aimed at different penalties relating to the proportionality of punishment under applicable constitutional rules. Judge, decision-making mechanism by the Panel of Judges, and indicted conditions. the criminal law factor is the principle of proportionality in decision making. Secondly, indicated in perpetrators of crime, crime victims. In this case, the Judge must play a role in determining matters relating law, even if the constitutional rule is unable to resolve.